Hierarchically Structured Zeolites: From Design to Application - Chen, Li-Hua; Sun, Ming-Hui; Wang, Zhao; Yang, Weimin; Xie, Zaiku; Su, Bao-Lian (Chemical reviews, 2020)
Hierarchical zeolites combine the intrinsic catalytic properties of microporous zeolites and the enhanced access and transport of the additional meso- and/or macroporous system. These materials are the most desirable catalysts and sorbents for industry and become a highly evolving field of important current interests. In addition to the enhanced mass transfer leading to high activity, selectivity, and cycle time, another essential merit of the hierarchical structure in zeolite materials is that it can significantly improve the utilization effectiveness of zeolite materials resulting in the minimum energy, time, and raw materials consumption. Substantial progress has been made in the synthesis, characterization, and application of hierarchical zeolites. Herein, we provide an overview of recent achievements in the field, highlighting the significant progress in the past decade on the development of novel and remarkable strategies to create an additional pore system in zeolites. The most innovative synthesis approaches are reviewed according to the principle, versatility, effectiveness, and degree of reality while establishing a firm link between the preparation route and the resultant hierarchical pore quality in zeolites. Zeolites with different hierarchically porous structures, i.e., micro-mesoporous structure, micro-macroporous structure, and micro-meso-macroporous structure, are then analyzed in detail with concrete examples to illustrate their benefits and their fabrications. The significantly improved performances in catalytic, environmental, and biological applications resulting from enhanced mass transport properties are discussed through a series of representative cases. In the concluding part, we envision the emergence of "material-properties-by-quantitative and real rational design" based on the "generalized Murray's Law" that enables the predictable and controlled productions of bioinspired hierarchically structured zeolites. This Review is expected to attract important interests from catalysis, separation, environment, advanced materials, and chemical engineering fields as well as biomedicine for artificial organ and drug delivery systems.